2006
DOI: 10.1139/o05-149
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cholesterol and lipid metabolism on host cell structure and hepatitis C virus replication

Abstract: The hepatitis C virus (HCV) replicates on a membrane protein complex composed of viral proteins, replicating RNA, and altered cellular membranes. Small-molecule inhibitors of cellular lipid-cholesterol metabolism such as 25-hydroxycholesterol, cerulenin, lovastatin, and GGTI-286 all show a negative effect on HCV replication. Perturbation of host cell lipid and cholesterol metabolism can disrupt replication complexes by altering membranous structures where replication occurs. Changes in cholesterol and (or) lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 38 publications
(65 reference statements)
5
76
1
Order By: Relevance
“…These experiments were performed in cultured cells, and the concentrations of the inhibitor tested did not induce host cell toxicity or apoptosis [6]. Similar results have been obtained for DENV, yellow fever virus (YFV), WNV, and HCV using the FASN inhibitor C75 [9,81,102,119], or cerulenin, another FASN inhibitor [81,102,111]. HMCV, influenza A, DENV, YFV, and WNV are enveloped viruses.…”
Section: Inhibitors Of Fatty Acid Biosynthesis As Potential Antiviralsupporting
confidence: 57%
See 1 more Smart Citation
“…These experiments were performed in cultured cells, and the concentrations of the inhibitor tested did not induce host cell toxicity or apoptosis [6]. Similar results have been obtained for DENV, yellow fever virus (YFV), WNV, and HCV using the FASN inhibitor C75 [9,81,102,119], or cerulenin, another FASN inhibitor [81,102,111]. HMCV, influenza A, DENV, YFV, and WNV are enveloped viruses.…”
Section: Inhibitors Of Fatty Acid Biosynthesis As Potential Antiviralsupporting
confidence: 57%
“…Several studies have highlighted the role of the cholesterol and the cholesterol biosynthetic pathway in the replication of viruses, including important human pathogens belonging to the Flaviviridae family -WNV [90], DENV [110], and HCV [8,[111][112][113] Table 2. Examples of host cell genes associated to lipid metabolism and involved in viral replication associated to the infection of animal pathogens like African swine fever virus [115].…”
Section: Cellular Lipids Involved In Viral Replication Complex Assemblymentioning
confidence: 99%
“…Similarly to tombusviruses, the replication of other viruses, such as Dengue virus, Norwalk virus, and hepatitis C virus (HCV), also depends on sterols (6,18,46,47). It has been shown that the HCV replicase complex is associated with cholesterol-rich lipid rafts (2).…”
Section: Discussionmentioning
confidence: 99%
“…siRNAs targeting the mevalonate (diphospho) decarboxylase (MVD) enzyme, which catalyzes the formation of mevalonate, were found to inhibit Luc-1b replication (19). Inhibition of the cholesterol biosynthesis pathway and host cell geranylation has been previously reported to inhibit HCV subgenomic replication (3,24,51,62,67). siRNA-mediated knockdown of the class III phosphatidylinositol 4-kinases PI4KA and PI4KB inhibited luciferase expression not only for the genotype 1b subgenomic replicons (Luc-1a and Luc-1b) but also for the viral RNA levels of SG-1b, Luc-1b, and Luc-1a.…”
mentioning
confidence: 99%